Tensor products of abstract Besov spaces - Dmytryshyn, M.I. (Carpathian Mathematical Publications, 2012)
We prove the interpolation theorem for tensor products of abstract Besov spaces, associated with closed operators in Banach spaces and show its application to the problems of approximations of elements of tensor products of Banach spaces.